“Determinación de caudales máximos para definir áreas de protección ambiental en las riberas del río Cutuchi Latacunga” - Jiménez Molina, Evelyn Shervin (2023)
At present, the water bodies lose the degree of importance in their conservation by society and competent authorities in accordance with overexploitation, consumption and contamination in different agricultural and industrial activities. In addition, in recent decades anthropogenic activities have become the main problem of the transformation of ecosystems, modifying or destroying them in order to develop their activities. On the other hand, Ecuadorian legislation requires maintaining an ecological flow to preserve ecosystems and biodiversity. However, there are few rivers in the country in which the minimum flow has been established.